Análise da composição e distribuição geográfica dos atuns da costa brasileira (Perciformes: Scombridae: Thunnini) - Ramirez, Zoila Raquel Siccha [UNESP] (2015)
Tunas, bonitos and mackerels are marine pelagic fishes distributed in the tropical and subtropical oceans of the world. They are highly captured and traded throughout their distribution area being the eight species of the genus Thunnus those with higher commercial value. Correct species identification in fisheries is needed to take better conservation measures and efficient fisheries management. The results are discussed in two chapters, the first based on the identification of the species within the family Scombridae and the second testing population analysis in two species of tuna Katsuwonus pelamis and Thunnus obesus, offen captured in Brazil and Peru. For this, test the efficiency of the DNA barcode methology and amplification of the control region of species of the Scombridae family, with emphasis in the genus Thunnus, and the identification and separation of the populations of two tuna. Twenty species were analyzed with the COI (648 specimens) and eighteen with the D-loop (313 specimens). For the first part of the study, the COI gene discriminated 66% of the analyzed species, but those belonging to the genus Thunnus could not be separated, unlike the results found in the D-loop in which all species were properly separated and powerful tool for species identification of the Scombridae family, including genus Thunnus. In the population analysis (second chapter) using the D-loop was possible to identify two populations of T. obesus (Pacific and Atlantic), with a high value of Fst, highly structured and statistically significant and also of two populations of K.pelamis (clade I and clade II), but in this second case has not been verified a geographical isolation of populations